Slim hopes - Kilbourne, Jean; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 1995)
Slim Hopes offers an in-depth analysis of how female bodies are depicted in advertising images and the devastating effects of those images on women's health. Addressing the relationship between these images and the obsession of girls and women with dieting and thinness, the program offers a new way to think about life-threatening eating disorders such as anorexia and bulimia, and a well-documented critical perspective on the social impact of advertising
Title from title screen
Originally produced by the Media Education Foundation in 1995
Executive producer, director, editor, Sut Jhally ; director of photography, Charles Pappert ; research, Heather Odom ; camera, Charles Pappert, Scott Perry, Sut Jhally
Keywords: Body image in women -- Social aspects; Leanness -- Social aspects; Advertising -- Psychological aspects; Women in advertising